Enhancement of archaeological sites and human remains in decentralized areas: territorial expansion and ethical education through the involvement of students. - Vanni, Arianna; Fusco, Roberta (Medicina Historica, 2023)
The enhancement of archaeological sites with human remains is an essential practice to preserve and understand our past, but these realities also constitute a unique opportunity to involve both the community and especially the students in stimulating and interdisciplinary lessons. The "Archaeological Itinerary of the Valcuvia territory", with its focus on the recovery of human remains from peripheral archaeological sites, is a virtuous example of the use of innovative teaching strategies, activating information and training courses on the various historical, archaeological, anthropological and ethical problems, through the history of ancient populations.